ECONOMIC JOURNAL OF EMERGING MARKETS : Mapping Food Availability and Food Scarcity in Migrants’ Hometown - Didit Purnomo, Indah Susilowati, dkk. (Fak. Ekonomi UII, 2014)
food availability, food security, food scarcity and surplus, central migrant